2023
DOI: 10.1093/plphys/kiad195
|View full text |Cite
|
Sign up to set email alerts
|

Plant extracellular self-DNA inhibits growth and induces immunity via the jasmonate signaling pathway

Abstract: Plants have evolved sophisticated mechanisms to detect various forms of danger. Damage-associated molecular patterns (DAMPs) are endogenous danger molecules that are released from damaged cells and activate the innate immunity. Recent evidence suggests that plant extracellular self-DNA (esDNA) can serve as a DAMP molecule. However, the mechanisms by which esDNA functions are largely unknown. In this study, we confirmed that esDNA inhibits root growth and triggers reactive oxygen species (ROS) production in a c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
20
1

Year Published

2023
2023
2025
2025

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 74 publications
2
20
1
Order By: Relevance
“…The levels of JA peaked at 30 min and those of SA at 24 h ( Figure 2 ; Supplementary Figure S3 ). Subsequent treatments revealed self/nonself-specific effects of DNA on H 2 O 2 and both hormones and in all cases, strongest effects were triggered by self-DNA ( Figure 2 ), similar to earlier observations, although with minor differences between species ( 20 22 , 26 , 35 , 36 ). The response times and levels reached by the three signals fall clearly within the standard kinetics of the three signals ( 119 121 ).…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…The levels of JA peaked at 30 min and those of SA at 24 h ( Figure 2 ; Supplementary Figure S3 ). Subsequent treatments revealed self/nonself-specific effects of DNA on H 2 O 2 and both hormones and in all cases, strongest effects were triggered by self-DNA ( Figure 2 ), similar to earlier observations, although with minor differences between species ( 20 22 , 26 , 35 , 36 ). The response times and levels reached by the three signals fall clearly within the standard kinetics of the three signals ( 119 121 ).…”
Section: Discussionsupporting
confidence: 89%
“…Strikingly, stronger responses to self- in comparison to nonself-DNA were reported in most, although not all, of the studies that compared DNA from different sources. Even the ‘Mazzoleni-effect’ – a dosage-dependent inhibition of growth by self-DNA, but not nonself-DNA that has been described originally by the group of Stefano Mazzoleni – could subsequently be confirmed in different models, including a tree ( Alnus glutinosa ), freshwater and marine algae and the nematode, Caenorhabditis elegans ( 18 , 21 , 22 , 30 , 31 , 35 , 37 , 38 ). Differential responses to self- versus nonself-DNA are significant even when nonself-DNA from closely related genotypes (species of the same genus or ecotypes of the same species) is used ( 21 , 26 , 31 , 35 , 36 , 38 ).…”
Section: Introductionmentioning
confidence: 92%
See 2 more Smart Citations
“…Extracellular ATP (eATP) has been shown to play multiple roles in plant growth and development, including root growth and stress responses [6,18,20,40,41]. It has been reported that eATP suppresses growth and alters the growth orientation of the root and hypocotyl of Arabidopsis by affecting hormone signaling pathways [6,[41][42][43][44]. Some reports suggest that the P2K1 receptor is partially involved in eATP-mediated plant growth [44].…”
Section: Discussionmentioning
confidence: 99%